THE INFLUENCE OF FINANCIAL PERFORMANCE ON PROFITABILITY (CASE STUDY OF SUB SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2018 - 2020) - Rian Rahmat Ramadhan; Veranda Veranda; Dwi Dewisri Kinasih (LPPM Press STIE Indragiri Rengat, 2022)
This research aims to find out and analyze the influence of financial performance on profitability. This research uses quantitative studies using purposive sampling techniques with a sample count of 10 companies. The subject of this study is an automotive sub-sector company listed on the Indonesia Stock Exchange for the period 2018-2020. The results showed that there was no effect of Debt to Equity Ratio (X₂) and Firm Size (X₄) on Profitability (Y) in automotive sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2020. However, there is a positive influence of Current Ratio (X₁) and Total Asset Turnover (X₃) on Profitability (Y) in automotive sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2020.